1969
DOI: 10.1136/bjo.53.6.403
|View full text |Cite
|
Sign up to set email alerts
|

Ocular penetration of cephalexin in the rabbit.

Abstract: The cephalosporin group of antibiotics has gained widespread use in combating resistant infections. Because of the necessity for intravenous administration of cephalothin, and the intramuscular route for cephaloridine, the development of a new member of this series which is effective orally prompted study of its penetration into the eye. This is the first reported study of the passage of cephalexin into the aqueous humour. Material and methodsCephalexin was provided in pure powdered form by the manufacturer th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1969
1969
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 2 publications
0
4
1
Order By: Relevance
“…This is characteristic of a poorly lipophilic drug. Cephalexin has previously been shown to penetrate into the aqueous humor of noninflamed rabbit eyes at concentrations as high as 15-20% of plasma concentrations (Gager et al, 1969). However, the difference between the study in rabbits and in these horses is that the rabbits were administered a higher dose (50 mg/kg) and the aqueous levels peaked at 1 h after dosing, which was earlier than the sampling times of the horses in the present study.…”
Section: Cephalexin In Horses 429contrasting
confidence: 56%
See 1 more Smart Citation
“…This is characteristic of a poorly lipophilic drug. Cephalexin has previously been shown to penetrate into the aqueous humor of noninflamed rabbit eyes at concentrations as high as 15-20% of plasma concentrations (Gager et al, 1969). However, the difference between the study in rabbits and in these horses is that the rabbits were administered a higher dose (50 mg/kg) and the aqueous levels peaked at 1 h after dosing, which was earlier than the sampling times of the horses in the present study.…”
Section: Cephalexin In Horses 429contrasting
confidence: 56%
“…This is characteristic of a poorly lipophilic drug. Cephalexin has previously been shown to penetrate into the aqueous humor of noninflamed rabbit eyes at concentrations as high as 15–20% of plasma concentrations (Gager et al. , 1969).…”
Section: Discussionmentioning
confidence: 99%
“…e ionization states of CEX molecules vary with pH in the aqueous solution [26,27]. It is positively charged below its isoelectric point of 4.3 and negatively charged above pH 4.3 [15]. e pH of ZnSO 4 solutions is around 3.0.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Cephalexin (CEX, Figure 1) is hydrosoluble cephalosporins antibiotics. CEX is an amphoteric compound, and its isoelectric point was 4.3 [15]. e conventional methods currently used to extract CEX include liquid-liquid extraction [16], ultra�ltration [17], deproteination by organic solvent [18], solid-phase extraction [19,20], and liquid membrane extraction [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous pharmacological studies have reported only limited d r u g uptake b y the eye after local instillation (Barry a n d Rousseau 1969, Barza et al 1973, Furgiuele 1967, Gager et al 1969, Janes and Stiles 1963, Levine a n d Aronson 1970). D r u g s incorporated into liposomes, however, appear to penetrate better into the eye a n d to have higher local concentrations.…”
Section: Introductionmentioning
confidence: 97%